Builder's reference book - Black, Leslie (International Thomson Publishing, 1980)
A comphensive guide to information sources relevant to the building industry and legislation affecting it. It is designed for use as a tool either in the office or on site, giving facts in a compendium style to meet the most common requirements of the busy builder.